Fueling entrepreneurship in STEM: Unveiling trends, educational programs, and their impact - M. Eval Setiawan; Hadi Suwono; Hadi Nur; Sulisetijono Sulisetijono; Husamah Husamah (Social Sciences and Humanities Open)
Entrepreneurship concepts and practices have been integrated into STEM education. However, pedagogical strategies are important for developing an in-depth understanding. This study integrates critical insights from a systematic literature review (SLR) to develop a comprehensive understanding of the integration of entrepreneurship into STEM education. This SLR investigated research published in Scopus-indexed journals, explored research trends, pedagogical program structures, and assessed the impact of entrepreneurship education on STEM. The search phrase was “Entrepreneurship STEM.” The results were refined with the term “education.” We identified 605 publications in the Scopus database, of which only 60 met the inclusion criteria for the systematic review. These findings indicate a growing trend in research from 2012 to 2022. Researchers are attempting to understand how entrepreneurship can be integrated into STEM education in secondary schools and higher education through classroom learning and training. Entrepreneurship is taught through experiential learning and an interdisciplinary approach to build entrepreneurial skills and practices in STEM. Experiential learning has been widely implemented to bridge theoretical concepts with practical entrepreneurial skills. Interdisciplinary courses that combine technical knowledge with entrepreneurial principles emphasize real-world applications, problem-solving, and innovation. Assessment methodologies must move beyond competency-based evaluations, including business pitch competitions, prototype projects, and industry-validated assessments. Strengthening collaboration between industry and academia is also essential, as partnerships with startups, incubators, and technology firms can provide students with mentorships, internships, and direct exposure to entrepreneurial ecosystems.